IDENTIFIKASI PERTIMBANGAN PEMILIHAN KOMPONEN PENYUSUN AGROFORESTRI SALAK DI DESA SIATARATOIT KECAMATAN ANGKOLA BARAT KABUPATEN TAPANULI SELATAN - Mikrajni Harahap; Muhammad Mardhiansyah; Viny Volcherina Darlis (JURNAL ILMU-ILMU KEHUTANAN, 2021)
Salacca sumatrana Becc is one of the  Salacca zalacca which has been widely known to the public, especially in North Sumatra. Sitaratoit village is one of the  Salacca sumatrana Becc producing areas, which each household has  Salacca sumatrana Becc fields planted on its own as well as inherited from the family. The farmers decision on species selection was important as a consideration for developing agroforestry patterns in the future because risk factors were always present in each selection specific tree species. The purpose of this study was to identify the basis component selection of Salacca sumatrana Becc agroforestry based on community perceptions in Sitaratoit Village. The research data was obtained from in-depth interviews conducted in Sitaratoit Village using the purposive sampling method. This research showed that based on cultural, economic and ecological factors, the constituent components of  Salacca sumatrana Becc agroforestry in Siataratoit village were as follows: Salacca sumatrana Becc as the main commodity, Hevea brasiliensis, Durio zibethinus, and Persea americana as a shade tree and protective tree, Gmelina arborea and Toona sinensis as a land divider.